Asymmetric cross-hemispheric connections link the rat anterior thalamic nuclei with the cortex and hippocampal formation. (4th May 2017) - Mathiasen, Mathias L.; Dillingham, Christopher M.; Kinnavane, Lisa; Powell, Anna L.; Aggleton, John P.
Highlights: Thalamocortical projections from ATN are ipsilateral with the exception of a restricted bilateral AV projection to RSC. Corticothalamic projections to the ATN are bilateral with the exception of an ipsilateral Cg projection to the AV nucleus. The subiculum receives ipsilateral ATN efferents and provides the ATN with bilateral afferents. The LD nucleus has exclusively ipsilateral, bidirectional connections with investigated cortical and hippocampal targets. The postsubiculum has exclusively ipsilateral, bidirectional connections with the ATN, as well as the LD nucleus. Abstract: Dense reciprocal connections link the rat anterior thalamic nuclei with the prelimbic, anterior cingulate and retrosplenial cortices, as well as with the subiculum and postsubiculum. The present study compared the ipsilateral thalamic-cortical connections with the corresponding crossed, contralateral connections between these same sets of regions. All efferents from the anteromedial thalamic nucleus to the cortex, as well as those to the subiculum, remained ipsilateral. In contrast, all of these target sites provided reciprocal, bilateral projections to the anteromedial nucleus. While the anteroventral thalamic nucleus often shared this same asymmetric pattern of cortical connections, it received relatively fewer crossed inputs than the anteromedial nucleus. This difference was most marked for the anterior cingulate projections, as those to the anteroventral nucleus remained almost entirely ipsilateral. Unlike the anteromedial nucleus, the anteroventral nucleus also appeared to provide a restricted, crossed projection to the contralateral retrosplenial cortex. Meanwhile, the closely related laterodorsal thalamic nucleus had almost exclusively ipsilateral efferent and afferent cortical connections. Likewise, within the hippocampus, the postsubiculum seemingly had only ipsilateral efferent and afferent connections with the anterior thalamic and laterodorsal nuclei. While the bilateral cortical projections to the anterior thalamic nuclei originated predominantly from layer VI, the accompanying sparse projections from layer V largely gave rise to ipsilateral thalamic inputs. In testing a potentially unifying principle of anterior thalamic – cortical interactions, a slightly more individual pattern emerged that reinforces other evidence of functional differences within the anterior thalamic and also helps to explain the consequences of unilateral interventions involving these nuclei.